Data-Based Planning Assistance on Education Report Cards for Quality Schools in Madiun Regency Education Units - Rosyida Nurul Anwar (Journal Ligundi of Community Service, 2025)
Background. Data-Based Planning is a strategy for using data in the Education Report platform, which is used as an intervention effort by educational units, education offices, and local governments to improve the quality and achievement of education. The purpose of Data-Based Planning is to enhance the quality of education. Using the education unit budget, data-based Planning is carried out in educational units to improve the quality of education services. Purpose. This community service aims to strengthen and assist academic units regarding data-based Planning on the education report platform. Method. The activity was implemented in educational units in the Madiun Regency. There were 40 participants, including school principals, teachers, and supervisors. The implementation method was carried out using lecture and discussion methods. Results. The results of the activity implementation showed that educational units were able to carry out data-based Planning in the education report and carry out the Annual Work Plan (RKT) and ARKAS. Conclusion. Data-based Planning is part of increasing transparency, accountability, and efficiency in the education system to create quality schools.